Towards an ethics of spatiality - Zamora-Sauma, Rocío (2022)
From Jacques Derrida's deconstructive perspective, I am interested in identifying and rethinking some of the paradigms that mediate the forms of conceptualization of space. Particularly, I seek to identify how the Newtonian conception of space as a container survives, since colonial modernity, in the definition of territory and nation, having ethical and political effects in dealing with migrants and people in search of refuge. A philosophical, spatial, and ethical perspective on this would make it possible to criticize the idea of the container in which the relationship between territory, identity and nation continues to be imprisoned. I argue that it must be rethought by deconstructing the oppositions between being and appearance that underlie other disjunctions, among them, those of the interior/exterior or the body/soul dualism.